Steroid receptor–DNA interactions: toward a quantitative connection between energetics and transcriptional regulation - Bain, David L. (Oxford University Press, 2014)
Steroid receptors comprise an evolutionarily conserved family of transcription factors. Although the qualitative aspects by which individual receptors regulate transcription are well understood, a quantitative perspective is less clear. This is primarily because receptor function is considerably more complex than that of classical regulatory factors such as phage or bacterial repressors. Here we discuss recent advances in placing receptor-specific transcriptional regulation on a more quantitative footing, specifically focusing on the role of macromolecular interaction energetics. We first highlight limitations and challenges associated with traditional approaches for assessing the role of energetics (more specifically, binding affinity) with functional outcomes such as transcriptional activation. We next demonstrate how rigorous in vitro measurements and straightforward interaction models quantitatively relate energetics to transcriptional activity within the cell, and follow by discussing why such an approach is unexpectedly effective in explaining complex functional behavior. Finally, we examine the implications of these findings for considering the unique gene regulatory properties of the individual receptors.